SUPPORTING FIRST GRADE STUDENTS' UNDERSTANDING OF ADDITION UP TO 20 USING TRADITIONAL GAME - Farida Nursyahidah; Ratu Ilma Indra Putri; Somakim Somakim (Journal on Mathematics Education, 2013)
This research aim is to know the students' understanding in adding number up to 20 using traditional game of dakocan and to acquire learning trajectory of adding number up to 20 using traditional game of dakocan for the first grade of primary school. This research used methodology of design research that consists of three phases, there are preliminary design, teaching experiment, and retrospective analysis. Subject of this study is 33 first grade students of Sekolah Dasar Negeri (SDN) 98 Palembang as one of partners' school of Pendidikan Matematika Realistik Indonesia (PMRI). The result of this research shows that the students' understanding in adding number up to 20 can be stimulated by using traditional game of dakocan as a context. All of strategies and model that is used by students and also their result discussion shows how construction and contribution of students can help them to understand concept of adding number up to 20. All the activities that are done by students produce learning trajectory to gain the goal of learning. Each steps of learning trajectory of students has an important role in understanding the concept from informal to the formal level. Learning trajectory using dakocan that is produced consist of playing dakocan, put the model of dakocan to the frame ten dakomatika to understand the relation of part and whole of ten combination in adding number, and solving contextual problem in adding number up to 20.